Shaving ceremony for the groom - Mumbai Archive Project Team (Jio Institute, 2024)
Surrounded by female family members, the groom undergoes a shaving ceremony. Beyond its grooming purpose, this ritual harkens back to a time when marriages involved much younger couples. In earlier days, marriages often occurred at the onset of puberty, and a boy’s first shave marked his transition from boyhood to manhood.